2013
DOI: 10.1177/0271121413489172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tier 3 Phonological Awareness Intervention on Preschoolers’ Emergent Literacy

Abstract: This multiple baseline design study examined the effects of a Tier 3 early literacy intervention on low-income preschool children’s phonological awareness (PA). Seven preschool children who did not make progress on identifying first sounds in words during a previous Tier 2 intervention participated in a more intensive Tier 3 intervention. Children listened to stories and participated in early literacy activities led by an interventionist for approximately 15 min, 3 to 4 days per week for up to 8 weeks. Weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 47 publications
(62 reference statements)
3
26
0
Order By: Relevance
“…Based on the discussion above, it is clear that print and phonemic awareness is a necessary foundational skill that children must possess in order to become proficient readers (August & Shanahan, 2006;Edwards, & Taub, 2016;Ehri et al, 2001;Ehri & Nunes, 2002;Fitzpatrick, 1997;Liberman, Shankweiler, & Liberman, 1989;Morrow, 2009;Noe et al, 2014;Puranik et al, 2011;Snow et al, 1998;Torgesen, 1998). According to Liberman et al (1989), the most common cause of difficulties acquiring early word-reading skills is weakness in the ability to process phonological features.…”
Section: Importance Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the discussion above, it is clear that print and phonemic awareness is a necessary foundational skill that children must possess in order to become proficient readers (August & Shanahan, 2006;Edwards, & Taub, 2016;Ehri et al, 2001;Ehri & Nunes, 2002;Fitzpatrick, 1997;Liberman, Shankweiler, & Liberman, 1989;Morrow, 2009;Noe et al, 2014;Puranik et al, 2011;Snow et al, 1998;Torgesen, 1998). According to Liberman et al (1989), the most common cause of difficulties acquiring early word-reading skills is weakness in the ability to process phonological features.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…As educators increasingly are expected to implement evidence-based practice, or scientificallybased instruction (Bingham et al, 2016), in teaching children to read, more studies using various theoretical frameworks and methodologies measuring the effectiveness of various teaching methods are badly needed. When these studies show repeated positive results for learning, curriculum should move toward these types of instruction (Noe et al, 2014 , indicated that -learning to write is not just about learning the alphabet and sound-symbol relationship and putting them on paper; it is cognitive change for the child.‖ Language acquisition is a constructive process. The child constructs increasingly sophisticated language structures and sociolinguistic knowledge without being taught by adults in a formal way.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations